1989
DOI: 10.1073/pnas.86.9.3227
|View full text |Cite
|
Sign up to set email alerts
|

denV gene of bacteriophage T4 restores DNA excision repair to mei-9 and mus201 mutants of Drosophila melanogaster.

Abstract: The denV gene of bacteriophage T4 was fused to a Drosophila hsp70 (70-kDa heat shock protein) promoter and introduced into the germ line of Drosophila by Pelement-mediated transformation. The protein product of that gene (endonuclease V) was detected in extracts of heat-shocked transformants with both enzymological and immunoblotting procedures. That protein restores both excision repair and UV resistance to mei-9 and mus201 mutants ofthis organism. These results reveal that the denV gene can compensate for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Nucleic acid mutations which result from absorption of UV wavelengths can however be overcome by some bacteriophages, including phage T4, which have been found to carry their own repair genes, including denV for DNA excision repair 28 - 30 . With regards to the present study, further evaluation of the survivors of the 405 nm light-exposed phage population was out-with the scope of the study, however PDI and 405 nm light inactivation of viruses is thought to be due to Type I and Type II photoreactions, resulting in non-specific oxidative damage to structures such as the capsid, 31 therefore the potential for resistance development in exposed viruses, or other microorganisms, is unlikely 20 , 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Nucleic acid mutations which result from absorption of UV wavelengths can however be overcome by some bacteriophages, including phage T4, which have been found to carry their own repair genes, including denV for DNA excision repair 28 - 30 . With regards to the present study, further evaluation of the survivors of the 405 nm light-exposed phage population was out-with the scope of the study, however PDI and 405 nm light inactivation of viruses is thought to be due to Type I and Type II photoreactions, resulting in non-specific oxidative damage to structures such as the capsid, 31 therefore the potential for resistance development in exposed viruses, or other microorganisms, is unlikely 20 , 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, certain prokaryotic DNA repair genes can function in eukaryotic cells (1,14,34). Indeed, we recently demonstrated that expression of the E. coli alkB gene in human cells confers the same alkylation-resistant phenotype as it does in E. coli, i.e., resistance to the S N 2, but not S N 1, alkylating agent (6).…”
mentioning
confidence: 99%
“…The Ada MTase also transfers methyl groups from methylphosphotriester DNA lesions to a second active-site cysteine residue, whereupon the Ada protein is transformed into an efficient transcriptional activator for the ada, alkA4, alkB, and aidB genes (19,34,38 Three prokaryotic DNA repair genes were previously introduced into mammalian cells, and their expression confers resistance to DNA-damaging agents. These are the T4 UV endonuclease (denV) gene (2,35,36), which provides UV resistance, and the E. coli ada (3,5,11,14,28) and ogt (9,39) genes, which provide alkylation resistance. Notably, DenV, 6255 on May 11, 2018 by guest…”
mentioning
confidence: 99%
“…These are the T4 UV endonuclease (denV) gene (2,35,36), which provides UV resistance, and the E. coli ada (3,5,11,14,28) and ogt (9,39) genes, which provide alkylation resistance. Notably, DenV, MTase) were gifts from R. B. Setlow, Brookhaven National Laboratories.…”
mentioning
confidence: 99%